A radical philosophy of Saint Paul - Breton, Stanislas (Insurrections: critical studies in religion, politics, and culture, 2011)
Dispossessed life : introduction to Breton's Paul / Ward Blanton -- Biographical outline -- Hermeneutics and allegory -- Jesus the Christ : faith and the law -- The Pauline cosmos -- The church according to Saint Paul -- The cross of Christ